Signal processing techniques for array synthesis, beamforming, direction finding and calibration - Ng, Boon Poh. (2009)
This thesis reports original work on the following five areas of array processing: i) array weight synthesis, ii) array geometry synthesis, iii) broadband adaptive array beamforming, iv) broadband direction finding and v) array calibration. In the area of array weight synthesis, a general and flexible method is proposed to synthesize arrays with various array beampatterns. The array used may be linear array, circular ring array, rectangular or circular planar array. The types of patterns achievable are minimum average sidelobe level designs and equi-sidelobe designs with or without null control. In particular, the proposed method is used to design circular ring array and circular planar array with equi-sidelobe response; and equi-sidelobe endfire array with high directional resolution.